2017
DOI: 10.1080/22423982.2017.1311535
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and weight among children in Nuuk, Greenland, at school entry

Abstract: Objective: To explore the possible association between weight class and prevalence of caries among children born 2005-2007, living in Nuuk, Greenland, at time of school entry.Design: A cross-sectional register study based on data from electronic medical records(EMR) and oral health data from public health and dental care facilities.Methods: Data from routine examinations of children at time of primary school entry, including height and weight, were obtained from the EMRs. Dental charts recording oral health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
(32 reference statements)
0
7
1
Order By: Relevance
“…However, there are several other confounding variables associated with both ECC and being overweight/obese such as lifestyle, genetic, and geographical factors. 33 The opposite relationship was seen by Shen et al 35 who found that children in China with higher weight-forage had lower progression of dental caries, based on findings of a longitudinal study. Additionally, Kennedy et al 32 reported that there was no association between being overweight and the prevalence of ECC, in a cross-sectional study in Canada.…”
Section: Ecc and Adverse Nutritional Status Assessed By Anthropometri...mentioning
confidence: 94%
See 1 more Smart Citation
“…However, there are several other confounding variables associated with both ECC and being overweight/obese such as lifestyle, genetic, and geographical factors. 33 The opposite relationship was seen by Shen et al 35 who found that children in China with higher weight-forage had lower progression of dental caries, based on findings of a longitudinal study. Additionally, Kennedy et al 32 reported that there was no association between being overweight and the prevalence of ECC, in a cross-sectional study in Canada.…”
Section: Ecc and Adverse Nutritional Status Assessed By Anthropometri...mentioning
confidence: 94%
“…physicochemical characteristics of drinking water including fluoride content. 33,34,74 A meta-analysis of 14 studies by Chen et al 26 showed no differences in dental caries between abnormal-and normalweight children in low-and middle-income countries. However, a significantly higher prevalence of dental caries was found among overweight children in high-income countries.…”
Section: Ecc and Adverse Nutritional Status Assessed By Anthropometri...mentioning
confidence: 99%
“…Body mass index (BMI) was calculated as kg/m 2 . Participants were categorised into age and gender-specific weight classes based on the norms from the International Obesity Task Force (IOTF) cut-offs for child overweight, obesity and thinness for children up to 18 years of age [10,11], which permitted comparisons of results with earlier studies from Greenland [7,9,[12][13][14], Canada [15], Denmark [16] the Nordic region [17], Australia [18,19], and the UK [19].…”
Section: Variablesmentioning
confidence: 99%
“…The major strength of the study is that 78% of eligible children in Nuuk were included children, and our data could be identified electronically. The protocol of this study was designed to allow a comparison with previous studies from Greenland and abroad [9,13,14].…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…In Vietnam, Nguyen YHT studies showed that ECC in children 3-5 years old accounted for 79.1% [6], and this rate of 4 years old children in Vo Truong Nhu Ngoc's study was 92% [7]. In addition, many studies have shown that the rate of ECC, S-ECC, dmft, and dmfs index in obese children was higher than in normal children [8][9][10]. In contrary, some studies have shown that the rate of tooth decay in obese children was lower than in normal or malnourished children [11].…”
Section: Introductionmentioning
confidence: 96%